Enhancing Design Thinking Skills through a Multi-Interaction Blended Project-Based Learning Model in Higher Education - Karuru, Perdy; Haris, Abdul; Asdar, Muhammad

(untitled) - Baso, R (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
This study develops a multi-interaction-based Project-Based Learning (PJBL) model to enhance design thinking skills among higher-education students in Indonesia. Addressing the challenges of the Education 4.0 era, the model emphasizes critical thinking, collaboration, and creativity, which are essential competencies for 21st-century learners. Guided by the ADDIE framework (Analyze, Design, Develop, Implement, Evaluate), the research used a mixedmethods design and involved 100 first-year students in an introductory physics course. Participants were divided into experimental and control groups. Instruments used included surveys, observation checklists, and student project evaluations. The implementation spanned eight weeks and covered all stages of the model. Ethical clearance was obtained, and efforts were made to ensure the instruments' validity and reliability. The findings indicate that the model significantly improves students’ design thinking skills, as demonstrated by statistical analysis and qualitative feedback. Key interactions included collaboration among students, lecturers, and external stakeholders such as industry partners. The model incorporated empathy, idea exploration, prototype development, and real-world project implementation. The study concludes that the model is academically effective, fosters motivation, and has broad potential Journal of Teaching and Learning 20(2) P. Karuru, A. Haris, M. Asdar, Surarni, & Baso R. 237 for application across higher education programs to develop innovative, adaptive graduates.